2008
DOI: 10.1111/j.1365-2753.2007.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence exerted on drug prescribing by patients’ attitudes and expectations and by doctors’ perception of such expectations: a cohort and nested case‐control study

Abstract: We conclude that, although doctors prescribe in accordance with what they believe their patients expect, in practice patients exert no influence on drug prescribing because their prescription expectations are misconstrued by doctors, who overestimate them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
3
21
0
Order By: Relevance
“…They concluded that in daily practice patients do not exert any influence on drug prescription because their prescription expectations are misconstructed by physicians who tend to overestimate them. 23 These results are in line with findings from Cockburn et al who found that, although patients had expectations regarding medication when visiting the physician, the doctors' opinions about the patient expectations were the strongest determinants of prescribing drugs. 24 A fourth factor potentially explaining the broad use of 5-ASA in CD could be that physicians are trying to obtain a placebo effect or to avoid time-consuming explanations of the rationale for not providing the patient with 5-ASA.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…They concluded that in daily practice patients do not exert any influence on drug prescription because their prescription expectations are misconstructed by physicians who tend to overestimate them. 23 These results are in line with findings from Cockburn et al who found that, although patients had expectations regarding medication when visiting the physician, the doctors' opinions about the patient expectations were the strongest determinants of prescribing drugs. 24 A fourth factor potentially explaining the broad use of 5-ASA in CD could be that physicians are trying to obtain a placebo effect or to avoid time-consuming explanations of the rationale for not providing the patient with 5-ASA.…”
supporting
confidence: 82%
“…24 A fourth factor potentially explaining the broad use of 5-ASA in CD could be that physicians are trying to obtain a placebo effect or to avoid time-consuming explanations of the rationale for not providing the patient with 5-ASA. 23 Our study has several strengths and also limitations. The first strength is the systematic evaluation of 5-ASA utilisation in a large national cohort.…”
mentioning
confidence: 99%
“…A number of studies have demonstrated that a physician's perception of patient expectations positively correlated with prescription rates (2,4,30). Furthermore, the physician's perception of the patient's expectation more strongly predicted antibiotic prescribing than the patient's actual preferences, suggesting that physicians tend to overestimate patients' expectations (26).…”
Section: Discussionmentioning
confidence: 99%
“…There is some data that physicians overestimate the extent to which patients expect a prescription [19], suggesting that other, possibly subconscious, reasons might also play a role. Placebo prescription in such a situation is not a case of deception, but a conflict between the professional integrity of the physician and the patient's wish [8].…”
Section: What Is a Placebo Intervention In Clinical Practice?mentioning
confidence: 99%